2010
DOI: 10.1186/1479-5868-7-66
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of sedentary behaviours in preschool children: a review

Abstract: BackgroundSedentary behaviour has been linked with a number of health outcomes. Preschool-aged children spend significant proportions of their day engaged in sedentary behaviours. Research into the correlates of sedentary behaviours in the preschool population is an emerging field, with most research being published since 2002. Reviews on correlates of sedentary behaviours which include preschool children have previously been published; however, none have reported results specific to the preschool population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
143
4
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(180 citation statements)
references
References 55 publications
20
143
4
4
Order By: Relevance
“…Previous research has also suggested higher screenviewing time in older children (21) . We also observed a high proportion of males watching TV in excess, unlike in three reviews with a variety of age groups which reported no gender differences (3,8,22) . Large variations for computer/games-console use between countries, such as older Estonian females v. Swedish ones (6?2 % and 0 % respectively), were found in our study.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Previous research has also suggested higher screenviewing time in older children (21) . We also observed a high proportion of males watching TV in excess, unlike in three reviews with a variety of age groups which reported no gender differences (3,8,22) . Large variations for computer/games-console use between countries, such as older Estonian females v. Swedish ones (6?2 % and 0 % respectively), were found in our study.…”
Section: Discussionmentioning
confidence: 77%
“…A large number of studies focus on TV viewing making it one of the most commonly examined sedentary behaviours (3,8) , although it might not necessarily reflect overall sedentary time (9) . Different patterns of PA and sedentary behaviours have been observed by age, gender and country (2,5,6) .…”
mentioning
confidence: 99%
“…According to the Finnish study by Nupponen, Halme, Parkkisenniemi, Pehkonen, and Tammelin (2010) the most popular equipment among 3-to 6-year-old children were bicycle, running shoes, skis and skates. Interestingly, boys more often than girls had access to physically active equipment (Nupponen et al, 2010).Screen time (e.g., TV viewing, electronic game playing and computer use) has been the most commonly examined SB in preschool children (Hinkley, Salmon, Okely, & Trost, 2010;Owen et al, 2010). However, it is clear that preschool children's TV viewing habits are complex (Cox, Skouteris, Dell´Aquila, Hardy, & Rutherford, 2012), and recent TV-time findings for younger children have been inconsistent .…”
mentioning
confidence: 99%
“…Hinkley, et al (19), señalan que este campo de investigación apenas está emergiendo y establecen la necesidad de identificar los factores asociados a este tipo de comportamientos sedentarios, con el fin de orientar adecuadamente las estrategias de intervención. Con esta base, se analizan a continuación los factores asociados en este trabajo.…”
Section: Discussionunclassified